2020
DOI: 10.2147/cmar.s258887
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circular RNA ITCH Suppresses Cell Proliferation but Induces Apoptosis in Oral Squamous Cell Carcinoma by Regulating miR-421/PDCD4 Axis</p>

Abstract: Background: Circular RNAs (circRNAs), a group of covalently closed non-coding RNAs, serve critical regulatory roles in many human cancers, including oral squamous cell carcinoma (OSCC). The purpose of this study was to investigate the functional role of circular RNA ITCH (circ-ITCH) in OSCC and the underlying mechanisms. Methods: RT-qPCR analysis was applied to detect the expression levels of circ-ITCH in OSCC tissues and cell lines. MTT assay and flow cytometer analysis were used to evaluate the effects of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Upregulated circITCH enhanced the toxicity of chemotherapeutic agents against drug‐resistant multiple myeloma cells [ 68 ]. Similarly, the expression level of circITCH was reduced in OSCC tissues and cell lines compared to adjacent normal tissues and human oral keratinocytes, and circITCH overexpression significantly inhibited OSCC cell proliferation and induced apoptosis [ 69 ]. Therefore, it can be speculated that circRNA can also mediate the toxicity of chemotherapeutic drugs on OSCC cells.…”
Section: Functions and Mechanisms Of Ncrnas In Drug Resistance Of Osccmentioning
confidence: 99%
“…Upregulated circITCH enhanced the toxicity of chemotherapeutic agents against drug‐resistant multiple myeloma cells [ 68 ]. Similarly, the expression level of circITCH was reduced in OSCC tissues and cell lines compared to adjacent normal tissues and human oral keratinocytes, and circITCH overexpression significantly inhibited OSCC cell proliferation and induced apoptosis [ 69 ]. Therefore, it can be speculated that circRNA can also mediate the toxicity of chemotherapeutic drugs on OSCC cells.…”
Section: Functions and Mechanisms Of Ncrnas In Drug Resistance Of Osccmentioning
confidence: 99%
“…Multiple circRNAs have been demonstrated to be involved in HNC development through the regulation of the proliferation process ( Figure 1 ). CircATRNL1 ( 40 ), hsa_circ_0007059 ( 41 ), circRNA_002178 ( 42 ), hsa_circ_0046263 ( 43 ), hsa_circ_0005379 ( 44 ), circUHRF1 ( 45 ), circPVT1 ( 46 , 47 ), circHIPK3 ( 48 , 49 ), circRNA_0000140 ( 50 ), circRNA_100290 ( 51 ), circDOCK1 ( 52 ), hsa_circ_0055538 ( 53 ), circITCH ( 54 ), hsa_circRNA_101036 ( 55 ), circCCND1 ( 20 ), circMYLK ( 56 ), CDR1as ( 17 , 57 , 58 ), circPKD2 ( 59 ), circLARP4 ( 60 ), hsa_circ_0042666 ( 61 ), hsa_circRNA_100533 ( 62 ), circMDM2 ( 63 ), circ_0067934 ( 64 ), circRPMS1 ( 65 ), circ-ZNF609 ( 66 , 67 ), hsa_circ_0072387 ( 68 ), circRASSF2 ( 38 ), hsa_circ_0023028 ( 69 ), circCTDP1 ( 70 ), circ_0008450 ( 71 ), circMATR3 ( 72 ), hsa_circ_0057481 ( 73 ), circ_0001742 ( 74 ), circ_0000218 ( 75 ), circ_0001971 ( 76 ), circCORO1C ( 77 ), hsa_circ_0109291 ( 78 ), hsa_circ_0036722 ( 34 ), hsa_circ_0002203 ( 79 ) and hsa_circ_0066755 ( 80 ) are associated with tumor proliferation ( Table 1 ).…”
Section: Circrnas Are Associated With Proliferation In Hncmentioning
confidence: 99%
“…Studies have found that PDCD4 inhibits FLIP-mediated tumor cell apoptosis. In addition, circ-ITCH can directly bind to miR-421 and block its inhibition of PDCD4 in OSCC and induce cell apoptosis ( 54 ). Endoplasmic reticulum stress is another way to induce apoptosis.…”
Section: Circrnas Are Associated With Proliferation In Hncmentioning
confidence: 99%
“…So it is necessary for RCC to find new circRNAs target. Among these circRNAs, circular RNA ITCH (circ-ITCH) acts as a tumor suppressor in the occurrence of several tumors, such as hepatocellular carcinoma [ 22 ], ovarian cancer [ 23 ], oral squamous cell carcinoma [ 24 ], cervical cancer [ 25 ], osteosarcoma [ 26 ], and prostate cancer [ 27 ]. But the role of circ-ITCH in ccRCC is not clarified now.…”
Section: Introductionmentioning
confidence: 99%